Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
0 to infinity Σsin(14/n) - sin(14/(n+1)) = sin14? why?
Infinite Σsin(14/n) diverges, so does Σsin(14/(n+1))... how come
infinite Σsin(14/n) - sin(14/(n+1)) = sin14?
3 Answers
- Randy PLv 76 years agoFavorite Answer
You have one summation sign, not two. That makes a big difference here.
Each term consists of the difference of two terms.
S1 = first term = sin(14) - sin(14/2).
S2 = sum of first 2 terms = sin(14) - sin(14/2) + sin(14/2) - sin(14/3) = sin(14) - sin(14/3)
S3 = sum of first 3 terms = sin(14) - sin(14/3) + sin(14/3) - sin(14/4) = sin(14) - sin(14/4)
etc
Sn = sum of first n terms = sin(14) - sin(14/(n+1))
lim (n->infinity) Sn = lim(n->infinity) sin(14) - sin(14/(n+1)) = sin(14)
You can't rearrange that one sum into the two separate diverging sums, because rearranging is only valid when the two individual sums converge.
Here's a more obvious (I hope) example.
Suppose a_n = n - n for all n?
Then obviously a_n = 0 for all n, and Sn = sum(k=1,n) a_n = 0, and lim(n->infinity) Sn = 0.
But can't I just rewrite sum(n - n) as sum(n) - sum(n), both of which diverge? Answer: no.
- 6 years ago
Expand it out
sin(14/1) - sin(14/2) + sin(14/2) - sin(14/3) + sin(14/3) - sin(14/3) + .... - sin(14/(n + 1))
n goes to infinity, so sin(14/(n + 1)) goes to sin(0), which is 0
Now we have:
sin(14/1) + 0 + 0 + 0 + 0 + ... + sin(0) =>
sin(14) + sin(0) =>
sin(14) + 0 =>
sin(14)
Telescoping series. Learn them, love them.
- ?Lv 76 years ago
Σ[n=0 to infinity] sin(14/(n+1)) = Σ[n=1 to infinity] sin(14/(n))
Σ[n=0 to infinity] sin(14/(n) - Σ[n=1 to infinity] sin(14/(n))
sin 14 + Σ[n=1 to infinity] sin(14/(n) - Σ[n=1 to infinity] sin(14/(n))
sin 14